Effective Methods of Teaching Speaking in Primary School - Mutalliyeva, Malika (Indonesian Journal Publisher, 2024)
It is crucial to remember that teaching young learners is quite different from teaching adult learners, and frequently require teachers to keep young learners engaged in the classroom at primary schools. A competent teacher should be able to encourage and engage his/her pupils. In order to develop speaking skills at primary schools interesting exercises and interactive assignments must be utilized by teachers as there are various issues that schoolchildren may encounter when teaching speaking in English classes. This article highlights effective methods of teaching speaking in primary schools.